2010
DOI: 10.1002/0471143030.cb0611s49
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Oxidatively‐Induced Clustered DNA Lesions Using a Novel Adaptation of Single Cell Gel Electrophoresis (Comet Assay)

Abstract: The two basic groups of complex DNA damage are double‐strand breaks (DSBs) and non‐DSB oxidatively‐induced clustered DNA lesions (OCDLs). The single‐cell gel electrophoresis (SCGE) or comet assay has been widely used for the detection of low levels of various types of DNA lesions including single‐strand breaks (SSBs), DSBs, and oxidized bases per individual cell. There are limited data on the use of the comet assay for the detection of non‐DSB clustered DNA lesions using different repair enzymes as enzymatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…One example is the inclusion of purified lesion-specific enzymes. These enzymes can convert otherwise undetectable base lesions into detectable strand breaks and abasic sites 1,[19][20][21] . A widely used example is the repair endonuclease formamidopyrimidine-DNA glycosylase (Fpg), which reveals oxidative DNA modifications 19,22 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One example is the inclusion of purified lesion-specific enzymes. These enzymes can convert otherwise undetectable base lesions into detectable strand breaks and abasic sites 1,[19][20][21] . A widely used example is the repair endonuclease formamidopyrimidine-DNA glycosylase (Fpg), which reveals oxidative DNA modifications 19,22 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…These enzymes can convert otherwise undetectable base lesions into detectable strand breaks and abasic sites 1,[19][20][21] . A widely used example is the repair endonuclease formamidopyrimidine-DNA glycosylase (Fpg), which reveals oxidative DNA modifications 19,22 . Because the enzyme digestion step is applied after cell lysis, the system can be treated the same way as a traditional agarose slide without alterations to the protocol.…”
Section: Representative Resultsmentioning
confidence: 99%
“…However, differences exist in microdistribution (single molecules and clusters of ROS produced by radiation vs. single molecules produced by endogenous processes), relative yield of specific products (mainly O 2 •− and H 2 O 2 produced by endogenous processes vs. • OH in highest yield in irradiated cells) and timing of production (chronic release of endogenous ROS versus instantaneous production during irradiation) [92], As a result, damage from metabolic ROS is randomly distributed in the DNA, radiation-induced DNA damage frequently occurs in clusters [93]. Whereas ∼ 1/3 of DNA damage from ionizing radiation (low LET type) emanates from direct interaction of DNA with the irradiating particle and 2/3 due to indirect effects (Fig.…”
Section: Primary Effects Of Ionizing Radiationmentioning
confidence: 99%
“…Techniques such as the ‘comet assay’ [93; 94] and newer techniques (e.g. gas chromatography, high pressure liquid chromatography, immunoassays) [4; 68] can distinguish gross DNA damage produced by ionizing radiation and damage from oxidative attacks.…”
Section: Primary Effects Of Ionizing Radiationmentioning
confidence: 99%
“…The concepts in DNA cluster quantification are simple, but their execution is technically and analytically demanding. Dr. Georgakilas' group, using novel adaptations of DNA gel electrophoresis, has been able to provide to the scientific community relatively easy and reliable methodologies for the detection of OCDLs in a variety of cell and tissues [3,[9][10][11] . In early 2007, Gollapalle et al [4] showed for the first time in vivo that X-rays can induce a radiation-delayed effect in mice several weeks after the initial irradiation.…”
Section: Detection Of Ocdls In Vivo: Potential Clinical Applicationsmentioning
confidence: 99%